Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A= \(\frac{\left(\sqrt{30}\right)^2-\left(\sqrt{29}\right)^2}{\sqrt{30}+\sqrt{29}}\)= \(\frac{1}{\sqrt{30}+\sqrt{29}}\)
B= \(\frac{\left(\sqrt{29}\right)^2-\left(\sqrt{28}\right)^2}{\sqrt{29}+\sqrt{28}}\)= \(\frac{1}{\sqrt{29}+\sqrt{28}}\)
Mà ta có \(\sqrt{30}+\sqrt{29}\)>\(\sqrt{28}+\sqrt{29}\)
Nên \(\frac{1}{\sqrt{30}+\sqrt{29}}\)<\(\frac{1}{\sqrt{29}+\sqrt{28}}\)
Suy ra A<B
a)1/7\(\sqrt{51}\)=\(\sqrt{\frac{51}{49}}\);1/9\(\sqrt{150}=\sqrt{\frac{150}{81}}=\sqrt{\frac{50}{27}}\)
\(\frac{51}{49}=1+\frac{1}{49}+\frac{1}{49}\);\(\frac{50}{27}=1+\frac{23}{27}>1+\frac{23}{36}>\)\(1+\frac{2}{36}=1+\frac{1}{36}+\frac{1}{36}\)
1/49<1/36 nên 51/49<50/27 =>1/7\(\sqrt{51}\)<1/9\(\sqrt{150}\)
b) \(\sqrt{2017}+\sqrt{2016}>\sqrt{2016}\)+\(\sqrt{2015}\)
=>\(\frac{1}{\sqrt{2017}+\sqrt{2016}}< \)\(\frac{1}{\sqrt{2016}+\sqrt{ }2015}\) <=> \(\sqrt{2017}-\sqrt{2016}< \sqrt{2016}\)-\(\sqrt{2015}\)
1.99281489 x 10^28
ủa k còn cách nào # ak =3